The Italian Version of SCORE‐15: Validation and Potential Use. Issue 4 (28th September 2019) - Paolini, Daniele; Schepisi, Luigi
Abstract : SCORE‐15 (Systemic Clinical Outcome and Routine Evaluation) is a 15‐item questionnaire for completion by family members aged 12 years and older to assess outcomes in systemic therapy. This study aimed to investigate (a) the psychometric properties and the internal consistency reliability of the Italian version of SCORE‐15, (b) clinical responsiveness, and (c) normative (Italian) criteria. Furthermore, (d) the study sought to evaluate the participants' representation of both their family and their problems, analyzing open‐ended questions included in the SCORE‐15. Data were collected from two clinical centers for 208 families ( n  = 507). Results confirmed the three‐factor structure (i.e., strengths, difficulties, and communication), a good internal consistency reliability, and indicated a cutoff threshold for the Italian version. Furthermore, results showed that SCORE‐15 is a good instrument for clinical responsiveness and that it can be used to explore the way in which family members describe their families and problems. Overall, SCORE‐15 is a brief, psychometrically robust family assessment instrument that may be used for both researchers and practitioners in several domains of clinical and social psychology. Abstract : El SCORE‐15 (Evaluación de Rutina y Resultados Clínicos de la Terapia Sistémica) es un cuestionario de 15 preguntas para que lo contesten los miembros de la familia mayores de 12 años a fin de evaluar los resultados de la terapia sistémica. Este estudio tuvo como fin investigar a) las propiedades psicométricas y la consistencia interna fiabilidad de la versión italiana del SCORE‐15, b) el grado de respuesta clínica y c) los criterios normativos (italianos). Además, (d) el estudio se propuso evaluar la representación de los participantes de su familia y sus problemas, analizando preguntas abiertas incluidas en el SCORE‐15. Se recopilaron datos de dos centros clínicos para 208 familias ( n = 507). Los resultados confirmaron la estructura de tres factores (p. ej.: puntos fuertes, dificultades y comunicación), una buena consistencia interna fiabilidad y indicaron un tope para la versión italiana. Además, los resultados demostraron que el SCORE‐15 es un buen instrumento para evaluar el grado de respuesta clínica y que puede utilizarse para analizar la forma en la que los familiares describen a sus familias y a sus problemas. En general, el SCORE‐15 es un instrumento de evaluación familiar breve y psicométricamente sólido que puede utilizarse tanto para los investigadores como para los profesionales en varias áreas de la psicología clínica y social. Abstract : SCORE‐15(系统性临床结果和日常评估量表)是一个用于在系统性治疗中评估结果的测量工具, 含有15个项目, 由12岁及以上年龄的家庭成员完成。本研究旨在调查 a)心理测量特性、内部一致性和意大利版的SCORE‐15的可信度, b)临床的反应性, c)正常(意大利)标准, 以及 d)本研究试图评价参与者对其家庭和问题的代表程度, 也对SCORE‐15 包括的开放式问题进行分析。数据来自两个医疗中心的208个家庭(n=507)。结果确认了三因素结构(即:优势, 困难和交流), 较好的内部一致性, 和可信度, 还指出了意大利版的截断临界点。研究结果表明SCORE‐15就临床响应效果而言是一个较好的工具, 可以用来探索家庭成员描述家庭和其家庭问题的方式。总体而言, SCORE‐15是个较简洁的, 心理测量功能强大的家庭评估工具, 研究者和从业医师都可以在好几个临床和社会心理学领使用之。